Development of thermal installation on the basis of the cascade heat pump for ensuring all thermal and refrigerating needs of the consumer - Parshukov, Vladimir; Efimov, Nikolay; Papin, Vladimir; Bezuglov, Roman; Ovechkin, Aleksei (Eastern-European Journal of Enterprise Technologies, 2018)
This article describes the developed and manufactured multifunctional heat point, which allows to supply heat and refrigeration energy to consumers. For effective operation, the heat point contains an automated control system that allows to direct heat flows in an optimal way. Development of this thermal point began because in Russia there are no complex researches on creation of systems of power supply on the basis of heat pumps now. There are some works which actually copy the western technologies. At the same time, features of climatic zones are not considered that is extremely important for the development of similar power stations. That is, earlier nobody created a product which equally well works in the conditions of the Southern regions and Far North. Thermal and hydraulic calculations of thermal point were executed. Coefficients of performance and resistance of the contours of the heat pumping plant were the results of these calculations. These calculations showed that the transformation coefficient on all contours is in the range from 3.352 to 4.884. Now starting tests of the thermal point which showed a regularity of the chosen design decisions and operability of the installation are carried out. The received results will be useful at projection of similar systems as the main characteristics of cascade heatpumping plants are received by a calculated path. The concrete received results of a research are as follows: – the multipurpose thermal point allowing to carry out heating – 25 kW, hot water supply – 5 kW, conditioning – 16 kW, ventilation of 25 kW is developed; – key indicators of thermal effectiveness of the power station, such as transformation coefficient, thermal rating etc are defined; – capacity of compact accumulators of warmth is determined. Heating with the temperature of 35 оС, within 12 hours of night-time requires the boiler tank of 2500 l whereas the accumulator on change phase of 300–500 l; – on the basis of the analysis of available renewable and secondary energy sources the structure of heat fluxes of the standard consumer with sources of excess warmth and points of its consumption is developed